Regulação da divergência folicular: sinalização intracelular e hormônio anti-mülleriano - Ilha, Gustavo Freitas (2014)
Follicular development occurs in wave like patterns in monovulatory species and is regulated by a complex interaction of gonadotropins with local intrafollicular regulatory molecules. In the first study, induction of co-dominant follicles in vivo with FSH treatment was used to study morphological mechanisms of selection of the dominant follicle in cattle. We determined the functional status of the STAT3, AKT and MAPK signaling pathways in granulosa cells of dominant (DF), subordinate (SF) and co-dominant (co-DF) follicles. We observed that the relative mRNA abundance of MAPK1/3 and AKT1/2/3 was significantly higher in granulosa cells of SFs than in DFs. However, there was a tendency for lower abundance of phosphorylated MAPK3/1 and AKT proteins in SFs granulosa cells. Relative abundance of mRNA and phosphorylated isoform of STAT3 was higher in granulosa cells of SFs than DFs and co-DFs. In line with this, SF granulosa cells had higher mRNA levels of LIFR and IL6ST, the two receptors involved in STAT3 activation. In summary, in the first study, we showed that atresia of SFs is associated with increased expression of LIFR and IL6ST, and activation of STAT3 in granulosa cells. These molecular features were absent in co-DF2, suggesting that FSH rescues co-DF2s through activation of MAPK and AKT, and inhibition of STAT3 pathways. In the second study, we investigated the regulation of AMH and its receptor (AMHR2) during follicular deviation and the effect of FSH-induced codominant follicles on AMH production in two in vivo models. In this study, we observed that AMH mRNA expression was similar in F1 and F2 before deviation (Day 2). On the other hand, the AMH mRNA levels were higher in DFs than SFs at the expected time (Day 3) and after (Day 4) deviation. There was no statistical difference at AMHR2 mRNA expression during the deviation process. However, AMHR2 tended to be more expressed in DFs than SFs after deviation (day 4). In the co-dominant model, AMH mRNA levels in granulosa cells were similar among the follicles within the groups. However, FSH supplemented follicles had more AMH abundance than control follicles. These data were complemented by AMH protein which was higher in FSH-supplemented follicles (co-DFs) and DFs than SFs. On the other hand, AMHR2 mRNA was higher in DFs than in SFs and similar between co-DFs. Our results from the second study suggest that AMH expression is regulated during follicular deviation, being stimulated by FSH, whereas AMHR2 is downregulated during advanced atresia.